Arts, culture and the making of global cities creating new urban landscapes in Asia - Kong, Lily; Ching, Chia-ho; Chou, Tsu-Lung (Edward Elgar Publishing, Inc., 2015)
This book is a welcome and timely analysis of how global economic and financial powerhouses in Asia also aim to become global cultural cities. It critically examines the tension between top-down policies implemented by strong states to boost urban culture, which are typically focused on the hardware of iconic venues, museums, and opera houses mostly designed by famous western architects, and the need for freedom to enable more organic cultural initiatives rooted in local practices.'--Robert C. Kloosterman, University of Amsterdam, the Netherlands. 'This book not only establishes the importance of cultural projects in crafting Asia's new global cities, it offers the first systematic comparison of both governmental plans and artists' actions in major urban sites from Beijing to Singapore. Whether art is viewed as an economic engine or a creative act, the authors show that it is a highly visible part of Asian societies that no one can ignore.'--Sharon Zukin, author of Naked City: The Death and Life of Authentic Urban Places. 'This volume makes two very significant contributions to the literature on Asian cities: it shifts the focus away from manufacturing and real estate as drivers of growth to the role of creativity in fostering the development of global cities; and it chronicles how arts and culture are changing the physical character of the cities studied. It is a highly welcome addition to our understanding of the dynamics of urban Asia and its increasing importance in generating global culture.'--Susan Fainstein, Harvard Graduate School of Design, US and author of The Just City. While global cities have mostly been characterized as sites of intensive and extensive economic activity, the quest for global city status also increasingly rests on the creative production and consumption of culture and the arts.